n2=(1+n)2+5

Simple and best practice solution for n2=(1+n)2+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n2=(1+n)2+5 equation:



n2=(1+n)2+5
We move all terms to the left:
n2-((1+n)2+5)=0
We add all the numbers together, and all the variables
n2-((n+1)2+5)=0
We add all the numbers together, and all the variables
n^2-((n+1)2+5)=0
We calculate terms in parentheses: -((n+1)2+5), so:
(n+1)2+5
We multiply parentheses
2n+2+5
We add all the numbers together, and all the variables
2n+7
Back to the equation:
-(2n+7)
We get rid of parentheses
n^2-2n-7=0
a = 1; b = -2; c = -7;
Δ = b2-4ac
Δ = -22-4·1·(-7)
Δ = 32
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{32}=\sqrt{16*2}=\sqrt{16}*\sqrt{2}=4\sqrt{2}$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-4\sqrt{2}}{2*1}=\frac{2-4\sqrt{2}}{2} $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+4\sqrt{2}}{2*1}=\frac{2+4\sqrt{2}}{2} $

See similar equations:

| -5a-3=5a+7 | | -12-2n=-4n-5+3n | | x+x3+x2+16=49 | | -13=x-3/4 | | 5y-8=2(3y+2) | | 7x+4+7x=-8+2x-6+6x | | 76-49=g | | 13=2m+5. | | -26-4n=6n | | –2=3(s+18)+–11 | | 16-8=h | | 5+3x+6-14=124 | | Z^2i-8=0 | | -3-8y=-27 | | x4+8=32 | | 5d(d2-8)=2 | | -4+1b+6b=9+8+4b | | 0,32y=48 | | 5p=21+ | | b+40=6b | | 3x*5x=450 | | 124=14-6x+x3+5 | | 3z+18=2z-10 | | 3x×5x=450 | | 0.12(2a–5)+3a=81 | | ٥+٢(n+١)=٢n | | -2-2x=-6+8x | | 18-3c=42 | | 2b+8=3b-9 | | 91-42=g | | (5x-10)=(2.5x) | | 3y-15=2y+6 |

Equations solver categories